A Comparison of the Reliability of Make Versus Break Testing in Measuring Palmar Abduction Strength of the Thumb - Lim, J.X.; Toh, R.X.; Chook, S.K.H.; Sebastin, S.J.; Karjalainen, T. (Journal of Hand and Microsurgery, 2014)
Previous studies have established the role of quantitative measurements of palmar abduction strength of the thumb (PAST). This study compares the reliability of the ‘make’ versus the ‘break’ test in measuring PAST in healthy volunteers. In a ‘make’ test, the body part being tested is positioned at the start of its range of motion and the participant is asked to exert his/her maximal force. In a ‘break’ test, increasing force is applied to a body part after it has completed its range of motion, until the joint being tested gives way. PAST was measured in both hands in 100 healthy volunteers using a handheld device. Two examiners measured PAST using both the ‘make’ and ‘break’ test to determine inter-rater reliability. The tests were repeated in 30 volunteers 6 weeks after the initial testing to determine intra-rater reliability. Our results showed that the ‘make’ test has better inter and intra-rater reliability.
Keywords: Abductor pollicis brevis; Break test; Carpal tunnel syndrome; Make test; Palmar abduction; Thumb abduction strength